1974
DOI: 10.2136/sssaj1974.03615995003800030042x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Content: Microwave Oven Method

Abstract: The moisture content of two soils was determined rapidly with a microwave technique. Equations were developed for estimating soil drying times for two soils of different texture at different moisture contents and for different sample sizes. Results indicate that drying soil by microwave oven also may have a limited use as a method for soil preparation prior to chemical analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…All chemical methods developed require calibration curves for each specific soil, which can be difficult in field construction if little knowledge of the native soil exists. The next progression in measurement of moisture content was the simultaneous development of the nuclear soil density and moisture gauge (Visvalingam et al, 1972) and the microwave oven moisture content test (Miller et al, 1974). Once developed, microwave and nuclear moisture methods were the leading technologies due to ease of use in field applications; however, the nature of both methods imposes significant challenges to their use in expeditionary field construction.…”
Section: Problemmentioning
confidence: 99%
“…All chemical methods developed require calibration curves for each specific soil, which can be difficult in field construction if little knowledge of the native soil exists. The next progression in measurement of moisture content was the simultaneous development of the nuclear soil density and moisture gauge (Visvalingam et al, 1972) and the microwave oven moisture content test (Miller et al, 1974). Once developed, microwave and nuclear moisture methods were the leading technologies due to ease of use in field applications; however, the nature of both methods imposes significant challenges to their use in expeditionary field construction.…”
Section: Problemmentioning
confidence: 99%
“…The soil samples were wetted up following the procedure mentioned above. Miller et al [24], and Routledge and Sabey [25] showed that the drying time in a microwave oven increased when increasing water content and increasing sample size. Sixty two subsamples containing around 70g of soil of the different textural classes studied were dried in the microwave oven.…”
Section: Thermal Properties and Hydrodynamics Of The Soilmentioning
confidence: 99%
“…Other methods proposed for the determination of water in soils include the use of heat generated by propane gas instead of an electric furnace or by using a volumetric method in combination with the specific gravity of soil (6,7). More recently, the use of a microwave oven as a source of heat for the determination of water content in soils has been proposed by Miller et al (8) and modified by Hankin and Sawhney (9). All these methods are tedious, time consuming, or require a large sample size for accurate determination of water.…”
Section: Introductionmentioning
confidence: 99%